The development of a clinical research educational training for community health workers using the joint task force for clinical trial competency framework - Yakubov, Amin; Pimenova, Dina; Ahmed, Alzahraa; Corvacho, Romelia; Madigan, Joanna; Naik, Jay; Lyu, Chen; McFarlane, Anita; Foster, Victoria; Haseltine, Megan; Trifonov, Alexandr; Cabrera, Ivette; et al. (Frontiers in Pharmacology, 2023)
Introduction: The NYU Clinical & Translational Science Institute, in collaboration with a number of community-engaged initiatives, developed a training for community health workers (CHWs) to enhance health literacy about clinical research. This innovative research training provides CHWs with a basic level of competency in clinical research to convey the importance of research to communities and better advocate for their health needs. CHWs are an underutilized resource to engage diverse populations in clinical research. The training also addresses the need to expand and diversify the clinical research workforce—integrating CHWs into research teams and connecting underserved populations with research opportunities to enhance quality of care. Methods: Structured individual interviews and focus group sessions were held with CHWs as well as clinical research faculty and staff to identify knowledge gaps in clinical research and identify best practices for educating community members on research. Using the Joint Task Force (JTF) for Clinical Trial Competency framework, an online course was developed consisting of 28 modules offered asynchronously for internal and external audiences. Topics include the fundamentals of clinical research, scientific concepts and research design, research ethics, study management, clinical study operations, communications, and teamwork, as well as the importance of diversity and equity in research and the barriers to participation. Results: Learning was evaluated using multiple choice questions after each module to ensure the fundamental level of knowledge was obtained. A separate survey, completed at the conclusion of the course, evaluated the quality of training. Discussion: The course aims to enhance the knowledge and skills of CHWs to help promote greater understanding of clinical research within the communities they serve, including the risks and benefits of clinical research and opportunities for participation. As members of the research team, community stakeholders can help design interventions tailored to the unique needs, culture, and context of their communities. In addition, this research training equips trainees with skills to engage the community actively, involving them in the research process and ensuring community priorities are represented in research through more community engaged processes.